Japan as number one : lessons for America - Vogel, Ezra F. (Cambridge, Mass. : Harvard University Press, 1979)
"Japan as Number One: Lessons for America" examines the functional significance of centripetal orientation as related to governmental bureaucracies, politics, private industry, basic education, welfare, and crime control. In essence Vogel attributes remarkable Japanese successes in these spheres to Japan's indigenous pattern of group orientation. His attention centers around an exploration of cultural and structural factors which have contributed to its industrial development and unprecedented economic growth, as illustrated by the fact that Japanese wages had exceeded American levels by 1978.
Includes index.
Includes bibliographical references: p. 259-265.
aia 09/04/2018
Loans
Keywords: Japan -- Social condition s-- 1945; Japan -- Economic conditions -- 1945; Japan -- Politics and government -- 1945; Japan